Faith and wisdom in science - McLeish, Tom (Oxford, United Kingdom : Oxford University Press, 2014)
"'Can you Count the Clouds?' asks the voice of God from the whirlwind in the stunningly beautiful catalogue of nature--questions from the Old Testament Book of Job. Tom McLeish takes a scientist's reading of this ancient text as a centrepiece to make the case for science as a deeply human and ancient activity, embedded in some of the oldest stories told about human desire to understand the natural world. Drawing on stories from the modern science of chaos and uncertainty alongside medieval, patristic, classical and biblical sources, Faith and Wisdom in Science challenges much of the current 'science and religion' debate as operating with the wrong assumptions and in the wrong space"--Book jacket
A clamour of voices -- What's in a name? Stories of natural philosophy, modern and ancient -- Creation, curiosity and pain: natural wisdom in the Old Testament -- Order and chaos: the comet, the storm and the earthquake -- At the summit: the Book of Job -- Creation and reconciliation: the New Testament creation narratives -- A theology of science? -- Mending our ways, sharing our science and figuring the future
Includes bibliographical references (pages 271-275) and indexes
Keywords: Bible and science; SCIENCE; creation and reconciliation; nature and cosmos; Natural philosophy; Book of Job